2019
DOI: 10.1016/j.scitotenv.2018.07.440
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of surface sludge deposits from fourteen French Vertical Flow Constructed Wetlands sewage treatment plants using biological, chemical and thermal indices

Abstract: Due to their design and mode of operation, French Vertical Flow Constructed Wetlands (VFCWs) accumulate suspended solids from the inflow wastewater in the form of a sludge layer at the surface of the first filter. In order to maintain the treatment performance over the long term, the characteristics of the sludge deposits and their evolution have to be well described. In this objective, a panel of sludge deposit samples taken from 14 French VFCW sewage treatment plants was investigated. Elemental composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Ozone, chlorine, UV radiation, and sodium hypochlorite are often used disinfectants. Due to its durability, monochloramine, which is employed to cleanse groundwater, is not utilized to treat wastewater [26][27][28]. (3) Determine the location of monitoring points.…”
Section: Methodsmentioning
confidence: 99%
“…Ozone, chlorine, UV radiation, and sodium hypochlorite are often used disinfectants. Due to its durability, monochloramine, which is employed to cleanse groundwater, is not utilized to treat wastewater [26][27][28]. (3) Determine the location of monitoring points.…”
Section: Methodsmentioning
confidence: 99%
“…The physical properties and organic matter composition of the selected sample was previously shown to be representative of a typology of surface deposits from French VFCW of more than 2-3 years of age (Kania et al, 2019;Kania et al 2018 a and b). The results obtained here firstly showed that only marginal proportions of the total contents in major elements and trace metals were leached from the surface deposits into the aqueous solution when the sample was contacted with water at the close-to-neutral pH obtained at thermodynamic equilibrium (pH 6.4).…”
Section: Discussionmentioning
confidence: 99%
“…The highlight this year for innovative technologies is on constructed wetlands for treatment of municipal sludge. In France, Kania, Gautier, Imig, Gautier, Imig, Michel, and Gourdon (2019) described a vertical flow constructed wetlands in 14 plants across the country to determine the impacts of aging on the sludge deposits within the wetland. The study showed those wetlands in operation one year or less had more abundant organic matter, less humified, and more biodegradable than more established wetlands (three years of operation or more) (Kania, Gautier, Imig, et al, 2019).…”
Section: Sludge To Biosolids: Treatment Advancesmentioning
confidence: 99%
“…In France, Kania, Gautier, Imig, Gautier, Imig, Michel, and Gourdon (2019) described a vertical flow constructed wetlands in 14 plants across the country to determine the impacts of aging on the sludge deposits within the wetland. The study showed those wetlands in operation one year or less had more abundant organic matter, less humified, and more biodegradable than more established wetlands (three years of operation or more) (Kania, Gautier, Imig, et al, 2019). To assess the ability of the sludge to retain specific elements including trace metals under both normal operating conditions and extreme pH conditions, samples from the wetlands noted above were examined for leaching (Kania, Gautier, Blanc, et al, 2019).…”
Section: Sludge To Biosolids: Treatment Advancesmentioning
confidence: 99%